Islamic Boarding School Management: A Comprehensive Analysis of a Special Program for Fostering Students' Disciplinary Character in Madrasah Ibtidaiyah - Hidayat, Wahyu; Hidayat, Nur (HEUTAGOGIA: Journal of Islamic Education, 2023)
This study investigates the role of Islamic Boarding School Management in fostering disciplined character among students at Madrasah Ibtidaiyah (MI) Al Ma'had An-Nur, utilizing a qualitative, descriptive approach. Data collection involved interviews, observations, and documentation, focusing on the disciplinary program's planning, implementation, and evaluation stages. The research highlights the Islamic Boarding School as a critical environment for continuous supervision and character development, embedding Quranic values in everyday life. The process involves three educational pillars: madrasah, family, and community, with learning experiences shaped through exemplary behavior and habituation. The study's findings show that at MI Al Ma'had An-Nur, disciplinary character development is executed through structured phases, incorporating goal setting, program implementation, continuous support, and rigorous evaluation. The school's approach integrates religious, educational, and communal elements, making it a powerful model for Islamic education. However, the study's focus on a single institution and reliance on qualitative data suggest broader research, including comparative studies and quantitative methods, to deepen understanding of Islamic Boarding School practices. The research serves as a reference for other Islamic schools in developing character development programs and contributes to the broader field of Islamic education.